PENGEMBANGAN STRUCTURE EXERCISE METHODE (SEM) DALAM MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SAINS PADA SISWA DI MADRASAH IBTIDAIYAH AL ISLAH KOTA GORONTALO - Rahmat, Abdul (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2016)
Exercise structure development method (sem) to enhance the activity and results in students learning science in elementary school. This research aims to improve the learning activities of students of class V MI Al Islah on the subject of style and improve learning outcomes fifth grade students of MI Al Islah on the subject of style. The method used in this research is classroom action research which in practice is done in two cycles with the re-assessment process cycle consists of four phases: planning, action, observation and reflection. The results obtained in this study is shown by the activities of learners are on the first cycle only increased by 61.25% to 80.63% in the second cycle. While the number of students who have mastery learning on the first cycle of 11 people and the second cycle increased by 29 persons and classical learning completeness in the second cycle reaches 100% in the second cycle, whereas in the first cycle of 37.93%. Thus it can be said that the Structure Exercise Method (SEM) is one of the alternative methods that can be used to increase the activity of learning and science learning outcomes of students.